Psychometric properties of Pediatric Quality of Life multidimensional fatigue scale in Italian paediatric cancer patients: A multicentre cross‐sectional study. (12th September 2021) - Rostagno, Elena; Marchetti, Anna; De Maria, Maddalena; Piazzalunga, Martina; Scarponi, Dorella; Zucchetti, Giulia; De Marinis, Maria Grazia; Piredda, Michela
Abstract: Objective: The original Pediatric Quality of Life–Multidimensional Fatigue Scale (PedsQL‐MFS) developed in 2002 in the English language is a frequently used tool in paediatric oncology. It has been translated into several languages, and the aim of this study was to test the psychometric properties of the Italian version of this scale in paediatric patients with cancer. Methods: This was a cross‐sectional validation multicentre study. Results: Acceptability was 100% for patients and 99.2% for parents. Confirmatory factor analysis of the three‐factor model of the original scale yielded poor fit indices. A three‐factor solution was found through exploratory structural equation modelling, with good fit indices. The internal consistency, evaluated through the Cronbach's alpha coefficient, ranged 0.71–0.92 for the total sample, both in the self‐report and in the proxy‐report questionnaire. Conclusion: The Italian version of the PedsQL‐MFS for children and adolescents with cancer shows adequate psychometric characteristics of both the self‐ and proxy‐report. Further research with larger samples is needed ensuring all age groups are appropriately represented.